Smallholder willingness to pay and preferences in the way irrigation water should be managed: a choice experiment application in KwaZulu-Natal, South Africa - Chipfupa, U; Wale, E (Water SA, 2019)
Efficient and sustainable utilization of irrigation water is the key to realizing the objective of enhancing agricultural productivity and commercializing smallholder irrigation farming. Valuing and recognizing the scarcity of irrigation water is essential for its sustainable use. Using cross-sectional data from 328 smallholders in and around Makhathini and Ndumo-B irrigation schemes in KwaZulu-Natal Province, the study aimed to assess smallholder farmers’ preferences for the way irrigation water resources should be managed and their willingness to pay for irrigation water. This was done employing a choice experiment method. The results suggest the need for irrigation water pricing to reflect irrigation intensity. They also show that improving agricultural production and productivity, with market access can enhance farmers’ willingness and ability to pay for irrigation water. The need to consider multiple uses of irrigation water for sustainable utilization of water resources is evident, while supporting women smallholders will have a positive impact on their willingness to pay for irrigation water. The paper recommends a shift towards on-farm volumetric water pricing in the irrigation schemes. The schemes should also have clearly defined boundaries and enforceable rules on collective use of water. The design of irrigation infrastructure should integrate other uses of irrigation water such as domestic and livestock purposes. Consequently, there is a need for further research to ensure that irrigation water prices reflect the marginal value of irrigation water use. Policies should address factors that inherently result in gender differences in terms of access to productive resources which negatively affect sustainable water utilization.